Ambient dose equivalent measurement with a CsI(Tl) based electronic personal dosimeter - Park, Kyeongjin; Kim, Jinhwan; Lim, Kyung Taek; Kim, Junhyeok; Chang, Hojong; Kim, Hyunduk; Sharma, Manish; Cho, Gyuseong (Nuclear engineering and technology, 2019)
In this manuscript, we present a method for the direct calculation of an ambient dose equivalent (H*(10)) for the external gamma-ray exposure with an energy range of 40 keV to 2 MeV in an electronic personal dosimeter (EPD). The designed EPD consists of a 3×3 mm2 PIN diode coupled to a 3×3×3 mm3 CsI (Tl) scintillator block. The spectrum-to-dose conversion function (G(E)) for estimating H*(10) was calculated by applying the gradient-descent method based on the Monte-Carlo simulation. The optimal parameters for the G(E) were found and this conversion of the H*(10) from the gamma spectra was verified by using 241Am, 137Cs, 22Na, 54Mn, and 60Co radioisotopes. Furthermore, gamma spectra and H*(10) were obtained for an arbitrarily mixed multiple isotope case through Monte-Carlo simulation in order to expand the verification to more general cases. The H*(10) based on the G(E) function for the gamma spectra was then compared with H*(10) calculated by simulation. The relative difference of H*(10) from various single-source spectra was in the range of ±2.89%, and the relative difference of H*(10) for a multiple isotope case was in the range of ±5.56%.